2018
DOI: 10.1002/nau.23535
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of non‐surgical management of detrusor leak point pressures above 40 cm water in adults with congenital neurogenic bladder

Abstract: A non-surgical protocol for ACU patients with NGB and dLPP/PMDP > 40, utilizing CIC, anticholinergics, and BTX is safe and effective when coupled with coordinated care and close follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Consistent with the reported 12-month success rates and effectiveness of IDB injection, Ladi-Seyedian et al [19] reported 1-, 2-, 3-, 5-and 6-year success rates of 75%, 45.5%, 37.5%, 33% and 29.1% in patients with UI due to neuropathic detrusor overactivity secondary to myelomeningocoele by the use of intravesical electromotive botulinum toxin type A administration. Whilst, Lane et al [20] documented that non-surgical protocol for patients with neurogenic bladders and detrusor leak-point pressures >40 cmH 2 O, including IDB injection in conjunction with anticholinergics is safe and effective, with a 3-year success rate of 85% In the present study, all patients received IDB injection of 100 U and the procedure resulted in no postoperative problems and this could be attributed to the small injected dose that minimised drug-induced side-effects without compromising the outcome. Also, the injection technique spared the trigone and sphincter to avoid postoperative outflow obstruction, and lastly, proper preoperative eradication of UTI and use of postoperative urinary antiseptics and broad-spectrum antibiotics prevented the possibility of postoperative infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the reported 12-month success rates and effectiveness of IDB injection, Ladi-Seyedian et al [19] reported 1-, 2-, 3-, 5-and 6-year success rates of 75%, 45.5%, 37.5%, 33% and 29.1% in patients with UI due to neuropathic detrusor overactivity secondary to myelomeningocoele by the use of intravesical electromotive botulinum toxin type A administration. Whilst, Lane et al [20] documented that non-surgical protocol for patients with neurogenic bladders and detrusor leak-point pressures >40 cmH 2 O, including IDB injection in conjunction with anticholinergics is safe and effective, with a 3-year success rate of 85% In the present study, all patients received IDB injection of 100 U and the procedure resulted in no postoperative problems and this could be attributed to the small injected dose that minimised drug-induced side-effects without compromising the outcome. Also, the injection technique spared the trigone and sphincter to avoid postoperative outflow obstruction, and lastly, proper preoperative eradication of UTI and use of postoperative urinary antiseptics and broad-spectrum antibiotics prevented the possibility of postoperative infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately the anticholinergic therapy is introduced as off-label in younger children. [6,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…At present, bladder augmentation represents the most effective way of surgical correction of the urinary bladder's functional parameters, leading to its increased capacity and decreased intravesical pressure. [12][13][14][15] In younger children the operative cystostomy provides an effective way to decrease intravesical pressures. [16,17] In the last years some reports have been published on the favourable results of Botulinum-A toxin (BTX) administration in patients with a low capacity, high pressure neurogenic bladder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations